2016
DOI: 10.1016/j.jinf.2016.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing antimicrobial therapy in children

Abstract: Management of common infections and optimal use of antimicrobial agents are presented, highlighting new evidence from the medical literature that enlightens practice. Primary therapy of staphylococcal skin abscesses is drainage. Patients who have a large abscess (>5 cm), cellulitis or mixed abscess-cellulitis likely would benefit from additional antibiotic therapy. When choosing an antibiotic for outpatient management, the patient, pathogen and in vitro drug susceptibility as well as tolerability, bioavailabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
3
1
3
Order By: Relevance
“…In both pediatric and adult UTI, extended antibiotic exposure has been associated with ecological disturbances in normal intestinal flora, the development of metabolic disturbances and obesity, increased rates of symptomatic UTI recurrence, and subsequent infections with more resistant pathogens. [20][21][22] Comparison of our observed 30-day recurrence rate of 5.5% with those reported in previous work is difficult because of methodological differences. Conway et al 23 found an annual rate of recurrence or reinfection of 12% per patient per year in a sample of children aged 6 years or younger, but that study had a mean follow-up of 408 days and included children with VUR.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In both pediatric and adult UTI, extended antibiotic exposure has been associated with ecological disturbances in normal intestinal flora, the development of metabolic disturbances and obesity, increased rates of symptomatic UTI recurrence, and subsequent infections with more resistant pathogens. [20][21][22] Comparison of our observed 30-day recurrence rate of 5.5% with those reported in previous work is difficult because of methodological differences. Conway et al 23 found an annual rate of recurrence or reinfection of 12% per patient per year in a sample of children aged 6 years or younger, but that study had a mean follow-up of 408 days and included children with VUR.…”
Section: Discussioncontrasting
confidence: 52%
“…In both pediatric and adult UTI, extended antibiotic exposure has been associated with ecological disturbances in normal intestinal flora, the development of metabolic disturbances and obesity, increased rates of symptomatic UTI recurrence, and subsequent infections with more resistant pathogens. 20-22…”
Section: Discussionmentioning
confidence: 99%
“…When antibiotics are indicated for the treatment of an odontogenic infection, empiric therapy with a broad-spectrum antibiotic is recommended. For abscesses larger than 5 cm, cellulitis or conditions with mixed abscess-cellulitis, drainage and administration of antibiotics are indicated [ 38 ]. Some studies have recommended the use of amoxicillin and metronidazole, or amoxicillin with clavulanic acid, as an empiric treatment for odontogenic infections.…”
Section: Resultsmentioning
confidence: 99%
“…1 A tetraciclina é considerada agente teratogênico e possui efeitos colaterais: um deles é o manchamento de dentes. [2][3][4][5] O manchamento dental causado pelo uso da tetraciclina depende da dose administrada, duração do tratamento e estágio do desenvolvimento dentário. 2,4,5 Isso ocorre devido à capacidade de formar um complexo com íons de cálcio, chamado de quelação.…”
Section: Introductionunclassified
“…[2][3][4][5] O manchamento dental causado pelo uso da tetraciclina depende da dose administrada, duração do tratamento e estágio do desenvolvimento dentário. 2,4,5 Isso ocorre devido à capacidade de formar um complexo com íons de cálcio, chamado de quelação. 6 Esse processo se dá entre a tetraciclina e íons de cálcio para formar complexos estáveis de ortofosfato de cálcio e tetraciclina, que são depositados nos ossos e dentes, sendo a dentina mais suscetível do que o esmalte.…”
Section: Introductionunclassified